Recent Therapies for Endometriosis: A Systematic Review - Putra, Ananda; Winata, Raymond Malvin; Berlianzsa, El-Varel Baby; Chandra, Angelica Isabella Monica; Manubulu, Charles Pauris; Tarigan, Tiara Namora; Ellyamurti, Devanti Octavia; Firdaus, Najmarani Devi; Risdiana, Dilla Alfinda (Medicinus, 2023)
Background: Endometriosis is a chronic gynecological disorder characterized by the growth of endometrial tissue outside the uterine cavity. It commonly affects women of reproductive age and is associated with chronic pelvic pain, dysmenorrhea, dyspareunia, and infertility. The disease significantly impacts productivity, social functioning, and sexual health, making it one of the leading causes of disability and reduced quality of life among women. Methods: This review was conducted through a literature search using databases such as PubMed, ScienceDirect, Google Scholar, and ResearchGate. Articles published between 2016 and 2025 were selected using the keywords endometriosis, hormonal therapy, and non-hormonal therapy. Relevant studies were analyzed, cross-referenced, and evaluated to identify current therapeutic strategies for endometriosis management. Result: The management of endometriosis currently includes both hormonal and non-hormonal therapies. Hormonal treatments involve the use of aromatase inhibitors, gonadotropin-releasing hormone (GnRH) analogues, selective estrogen receptor modulators (SERMs), selective progesterone receptor modulators (SPRMs), and dienogest, all aimed at suppressing estrogen production and endometrial growth. Non-hormonal therapies, on the other hand, utilize anti-inflammatory, anti-angiogenic, and pro-apoptotic mechanisms to target the inflammatory cascade that contributes to the pathogenesis of endometriosis. These therapies aim to reduce chronic inflammation, cell proliferation, and pain without interfering with ovulation or fertility. Conclusions: Both hormonal and non-hormonal therapies play a crucial role in managing endometriosis. While hormonal therapy remains the mainstay of treatment, non-hormonal approaches show promising results with fewer side effects and greater patient tolerability. However, further clinical studies are required to evaluate their long-term efficacy and safety before they can be widely implemented in clinical settings.